2006
DOI: 10.1177/000348940611501212
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Inflammatory Response and Scar Formation in Wounded Vocal Folds

Abstract: The results show a clear profile of vocal fold inflammation with corresponding changes in extracellular matrix production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(139 citation statements)
references
References 42 publications
6
131
0
2
Order By: Relevance
“…One application in the field of voice production is the characterization of viscoelastic properties of rat vocal fold tissue. Rats are commonly used animal models to study vocal fold biology and disease such as scarring and its treatments (Lim et al, 2006;Welham et al, 2008;Quinchia Johnson et al, 2010;Suehiro et al, 2010;Gugatschka et al, 2011). Characterization of the viscoelastic properties of rat tissue is difficult with other measurement methods such as tensile and rheology testing because of small sample size.…”
Section: B Perspectives For Future Workmentioning
confidence: 99%
“…One application in the field of voice production is the characterization of viscoelastic properties of rat vocal fold tissue. Rats are commonly used animal models to study vocal fold biology and disease such as scarring and its treatments (Lim et al, 2006;Welham et al, 2008;Quinchia Johnson et al, 2010;Suehiro et al, 2010;Gugatschka et al, 2011). Characterization of the viscoelastic properties of rat tissue is difficult with other measurement methods such as tensile and rheology testing because of small sample size.…”
Section: B Perspectives For Future Workmentioning
confidence: 99%
“…10,11 TGF-β gene expression increases as early as 8 hours after vocal fold injury and is maximal at 72 hours (the end point of the study). 11 In addition, hepatocyte growth factor has been shown to be an effective inhibitor of TGF-β-induced vocal fold fibrosis, both in vivo and in vitro. [12][13][14][15][16] A clinical report suggested that treatment with tranilast, a TGF-β inhibitor, reduced glottic fibrosis associated with intubation injury.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, however, excessive scar formation closes this pressure-reducing valve, thereby forcing the intraocular pressure to rise (5). Moreover, excessive scarring of the vocal folds may severely alter their ability to vibrate, thereby causing a number of voice disorders (6).…”
mentioning
confidence: 99%